2022
DOI: 10.3390/pr10071288
|View full text |Cite
|
Sign up to set email alerts
|

A Modification of the ABTS• Decolorization Method and an Insight into Its Mechanism

Abstract: A modification of the ABTS• decolorization assay for plate readers is presented. In our modification, 200 µL of ABTS solution of absorbance 1.0 at 734 nm was added with an antioxidant and decreased absorbance resulted. For comparison of antioxidant activities in the kinetic assay of absorbance decrease, concentration dependence of absorbance decrease and of area under curve are recommended. “Fast” and “slow” antioxidants were distinguished: while the reactions of “fast” antioxidants ABTS• were completed within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…This was observed because DPPH reacts with free radicals, but ABTS reacts with different free radicals, including peroxyl, hydroxyl, alkoxyl, and inorganic radicals, to form stable ABTS + type cationic radicals; due to having these differences, a difference in binding capacity to antioxidants occurred [41]. Therefore, ABTS + measured the antioxidant power of hydrophilic and hydrophobic substances, so it was judged to exhibit higher scavenging activity compared to DPPH [42]. The hydroxyl radical scavenging activity of fermented soybean yogurt and fermented soybean solid was estimated at 39% (500 µg/mL) and 49% (200 µg/mL) [43,44], which indicated higher amount compared to doenjang used in the study.…”
Section: Comparison Of Dna Damage Protecting Activity On Hdjs and Cdjsmentioning
confidence: 99%
“…This was observed because DPPH reacts with free radicals, but ABTS reacts with different free radicals, including peroxyl, hydroxyl, alkoxyl, and inorganic radicals, to form stable ABTS + type cationic radicals; due to having these differences, a difference in binding capacity to antioxidants occurred [41]. Therefore, ABTS + measured the antioxidant power of hydrophilic and hydrophobic substances, so it was judged to exhibit higher scavenging activity compared to DPPH [42]. The hydroxyl radical scavenging activity of fermented soybean yogurt and fermented soybean solid was estimated at 39% (500 µg/mL) and 49% (200 µg/mL) [43,44], which indicated higher amount compared to doenjang used in the study.…”
Section: Comparison Of Dna Damage Protecting Activity On Hdjs and Cdjsmentioning
confidence: 99%
“…ABTS and DPPH are radical scavenging‐based methods which generally have three mechanisms of antioxidants effect of phenolic compounds including hydrogen atom transfer, single electron transfer followed by proton transfer and sequential proton loss electron transfer (Munteanu & Apetrei, 2021; Gulcin & Alwasel, 2023). Usually, ABTS slow reactions with antioxidant were ascribed to hydrogen atom transfer, while fast ones were ascribed to single electron transfer reactions (Kut et al ., 2022). Gulcin & Alwasel (2023) reported that the reaction between DPPH and antioxidant depends on the difference in the ratio of mixed hydrogen atom transfer and single electron transfer mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…A modified [ 86 ] assay of Re et al [ 87 ] was used. Briefly, 200-μL aliquots of ABTS ● solution diluted with PBS to a concentration providing absorbance of 1.0 at 734 nm were pipetted to wells of a 96-well plate and added with 0–10 μL of the extracts or 0.5 mM Trolox, shaken, and left for 30 min at room temperature (21 ± 1 °C).…”
Section: Methodsmentioning
confidence: 99%
“…The antioxidant capacity of garlic and ramson extracts was calculated by comparing the slopes of dependencies of absorbance changes on the concentrations of Trolox and extracts as described previously [ 86 ] using the formula:…”
Section: Methodsmentioning
confidence: 99%